1997
DOI: 10.1002/cbm.157
|View full text |Cite
|
Sign up to set email alerts
|

Childhood experiences of patients with schizophrenia and a history of violence: a special hospital sample

Abstract: Certain childhood experiences, including deprivation and/or abuse, have been shown to contribute to the development of delinquency and later criminality. Although specific illness factors influence violent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 32 publications
(43 reference statements)
1
22
0
Order By: Relevance
“…Several studies have shown higher levels of insecure attachment in violent offenders than in the normal population (van IJzendoorn 1997;Frodi 2001;Adshead 2004;Levinson 2004;Bogaerts 2005). This evidence is supported by studies which show that offenders in prison or secure forensic institutions are more likely to report having experienced separations, abuse and neglect from their early caregivers than the general population (Coid 1992;Heads 1997;Weeks 1998).…”
Section: Attachment Studiesmentioning
confidence: 91%
“…Several studies have shown higher levels of insecure attachment in violent offenders than in the normal population (van IJzendoorn 1997;Frodi 2001;Adshead 2004;Levinson 2004;Bogaerts 2005). This evidence is supported by studies which show that offenders in prison or secure forensic institutions are more likely to report having experienced separations, abuse and neglect from their early caregivers than the general population (Coid 1992;Heads 1997;Weeks 1998).…”
Section: Attachment Studiesmentioning
confidence: 91%
“…37,38 Adults whose self-control is compromised by a current mental disorder might rely on violence if they had childhood conduct disorder, because they have extensive previous experience with fighting, bullying, and similar acts that victimize others.…”
Section: Violent Behaviors At 21 Years Of Agementioning
confidence: 99%
“…Among 426 rst admissions for psychosis in the USA, the prevalence of lifetime trauma exposure was 63%for men (24% child abuse) and 77%for women (44% child abuse) (Neria, Bromet, Sievers, Lavelle, & Fochtman, 2002). Even a chart review (which underestimates abuse rates; see Discussion) found that 52% of female, and 28% of male, patients diagnosed with schizophrenia in a British 'special hospital' had suffered 'parental violence against patient' (Heads, Taylor, & Leese, 1997). Of 5,362 children, those whose mothers had poor parenting skills when they were 4 were signi cantly more likely to be diagnosed schizophrenic as adults ( Jones, Rodgers, Murray, & Marmont, 1994).…”
Section: Clinical Diagnosesmentioning
confidence: 99%